1998
DOI: 10.1002/(sici)1097-0142(19980715)83:2<267::aid-cncr10>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative potential and K-ras mutation in epithelial hyperplasia of the gallbladder in patients with anomalous pancreaticobiliary ductal union

Abstract: BACKGROUND Recent studies have shown that anomalous pancreaticobiliary ductal union (APBD) is an important risk factor for the development of gallbladder carcinoma. Epithelial hyperplasia of the gallbladder is one of the characteristic changes, but it is not clear whether epithelial hyperplasia is a premalignant lesion that could lead to cancer in APBD patients. METHODS Twenty‐four APBD patients were classified into two types: patients with bile duct dilation (dilated type) (n = 13) and patients without dilati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(21 citation statements)
references
References 36 publications
2
19
0
Order By: Relevance
“…The biliary tract can be changed into a hyperplastic or dysplastic state due to repetitive stimulation of regurged pancreatic juice onto the bile duct mucosa, and these changes can cause cancerous changes in the mucosa [8,9]. Based on previous studies, these changes in the biliary mucosa can also occur in the patient with OPBR [2-5,10-14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biliary tract can be changed into a hyperplastic or dysplastic state due to repetitive stimulation of regurged pancreatic juice onto the bile duct mucosa, and these changes can cause cancerous changes in the mucosa [8,9]. Based on previous studies, these changes in the biliary mucosa can also occur in the patient with OPBR [2-5,10-14].…”
Section: Discussionmentioning
confidence: 99%
“…The Ki-67 labeling index is usually substantially greater in dysplastic lesions and increases in quantity with increasing degrees of dysplasia. It can also be marked in areas of regenerative change as well [8,12]. We found that high amylase level in the gallbladder was an important risk factor which causes inflammation and degeneration of the gallbladder mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of epithelial hyperplasia of the gallbladder of PBM patients without biliary dilatation was reported to be 72% to 91%. Tanno et al [32] reported that the Ki-67 labeling index of epithelial hyperplasia of PBM patients was elevated to 6.1%  ± 1.5% and K-ras mutation was detected in 2 (13%) of 15 patients. To detect PBM without biliary dilatation before onset of gallbladder cancer, we should perform MRCP for individuals showing gallbladder wall thickness on US [33].…”
Section: Pancreaticobiliary Maljunctionmentioning
confidence: 99%
“…Under this condition, the sphincter of Oddi can not regulate the outflow of bile and pancreatic juice, leading to two-way regurgitation [1, 2]. Frequent passage of pancreatic juice into the bile duct damages the epithelium of the biliary tract [3]. Bile reflux into the pancreatic duct could lead to pancreatitis.…”
Section: Introductionmentioning
confidence: 99%